Scapholunate Diastasis in Distal Radius Fractures: Fracture Pattern Analysis on CT Scans - Özkan, Sezai; Mudgal, Chaitanya S.; Jupiter, Jesse B.; Bloemers, Frank W.; Chen, Neal C. (Journal of Wrist Surgery, 2020)
Objectives Our understanding of distal radius fractures with concomitant scapholunate (SL) diastasis primarily comes from plain radiographs and arthroscopy. The clinical implications of SL diastasis are not clear. The aim of this study is to describe fracture characteristics of distal radius fractures on computed tomography (CT) scans in patients with distal radius fractures and static SL diastasis.Methods We queried our institutional databases to identify patients who were treated for a distal radius fracture, had a CT scan with a wrist-protocol, and static SL diastasis on their CT scan. Our final cohort consisted of 26 patients. We then collected data on their demographics, injury, treatment, evaluated injury patterns, and measured radiographic SL characteristics. Our study cohort consisted of 11 men (42%) and almost half of our cohort (n = 12; 46%) had a high-energy mechanism of injury. The majority of the patients (n = 20; 77%) had operative treatment for their distal radius fracture and two patients (7.7%) had operative treatment of their SL injury.Results The mean SL distance was 3.5 ± 1.1 mm. Twenty patients (77%) had an intra-articular fracture. In these patients, we observed three patterns: (1) scaphoid facet impaction; (2) lunate facet impaction; and (3) no relative impaction. We observed other injury elements including rotation of the radial styloid relative to the lunate facet and partial carpal subluxations.Conclusion Static SL dissociation in the setting of distal radius fractures may be an indication of a complex injury of the distal radius, which may not be directly apparent on plain radiography. If these radiographs do not demonstrate impaction of the lunate or scaphoid facet, a CT scan may be warranted to have a more detailed view of the articular surface.Level of Evidence This is a Level III, diagnostic study.
Keywords: distal radius fractures; injury pattern; CT scan; scapholunate diastasis